2017
DOI: 10.1016/j.biopsych.2016.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Brain Structure Biomarkers in the Psychosis Biotypes: Findings From the Bipolar-Schizophrenia Network for Intermediate Phenotypes

Abstract: GMD biomarkers depicted unique brain structure characteristics within Biotypes, consistent with their cognitive and sensorimotor profiles, and provided stronger discrimination for biologically driven biotypes than symptom-based diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
72
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 74 publications
9
72
1
1
Order By: Relevance
“…However, our GWAS on these structures' separate volumes did not have significant associations, which implies that the volumetric association may reflect joint regulation of part of the morphology of these structures. We noted that hippocampal volumes in our sample were significantly smaller in cases than in controls (ANOVA P=3E-06) [32][33][34], and there were also significant reductions in cases for the amygdala volumes (P=0.001), but not for the caudate. Gaser et al reported ventricular enlargement in schizophrenia associated with volumetric reduction of the thalamus and superior temporal cortex [30]; in our data, however, we did not observe significant correlation between the volumes of these structures and the volume of the temporal horn of lateral ventricle, or any detectable associations between these structures volumes and the CSF volume-associated genes.…”
Section: Significant Genetic Associations With Brain Csf Volumetric Vmentioning
confidence: 97%
“…However, our GWAS on these structures' separate volumes did not have significant associations, which implies that the volumetric association may reflect joint regulation of part of the morphology of these structures. We noted that hippocampal volumes in our sample were significantly smaller in cases than in controls (ANOVA P=3E-06) [32][33][34], and there were also significant reductions in cases for the amygdala volumes (P=0.001), but not for the caudate. Gaser et al reported ventricular enlargement in schizophrenia associated with volumetric reduction of the thalamus and superior temporal cortex [30]; in our data, however, we did not observe significant correlation between the volumes of these structures and the volume of the temporal horn of lateral ventricle, or any detectable associations between these structures volumes and the CSF volume-associated genes.…”
Section: Significant Genetic Associations With Brain Csf Volumetric Vmentioning
confidence: 97%
“…2 Duration of illness is calculated based on the date of the appearance of first positive symptoms of schizophrenia until the date of scan. 3 Antipsychotic treatment data is not available for all the patients included (82 patients had medication information). Cumulative doses were calculated per time of scan and given in chlorpromazine equivalents using standard conversion factors and estimated by the daily doses of each of the antipsychotics used by the patient.…”
Section: Disclosuresmentioning
confidence: 99%
“…The B-SNIP-1 dataset used in this study included 912 subjects after quality control assessment. Structural MRI three-dimensional acquisitions were carried out on 3T scanners (GE Signa, Philips Achieva, Siemens Allegra, and Siemens Trio) [21] [22]. High resolution isotropic T1-weighted MP-RAGE sequences were acquired following the Alzheimer's Disease Neuroimaging Initiative (ADNI) protocol [21,23].…”
Section: B-snip-1 Datasetmentioning
confidence: 99%